2019
DOI: 10.1097/ijg.0000000000001209
|View full text |Cite
|
Sign up to set email alerts
|

Initial Clinical Results of the eyeWatch: a New Adjustable Glaucoma Drainage Device Used in Refractory Glaucoma Surgery

Abstract: Précis: In this study, we report clinical results after implantation of an adjustable glaucoma drainage device. The intraocular pressure (IOP) profile was efficiently controlled postoperatively as the resistance to aqueous humor outflow was finely adjusted. Purpose: The main purpose of this study was to evaluate the safety and efficacy of the new adjustable glaucoma drainage device eyeWatch used in conjunction with a Baerveldt glaucoma implant in refrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…In that sense, obtaining comparable results after implantation of either a Baerveldt or an eyePlate indicates that these devices are functioning in a very comparable way to ensure a functioning filtering surgery. In other words, the efficacy and safety of the eyePlate are likely to be comparable to that of a Baerveldt device when connected to an eW 8 …”
Section: Discussionmentioning
confidence: 99%
“…In that sense, obtaining comparable results after implantation of either a Baerveldt or an eyePlate indicates that these devices are functioning in a very comparable way to ensure a functioning filtering surgery. In other words, the efficacy and safety of the eyePlate are likely to be comparable to that of a Baerveldt device when connected to an eW 8 …”
Section: Discussionmentioning
confidence: 99%
“…16 Roy et al have al-ready shown, in non-vitrectomized eyes, that the use of the eyeWatch device combined to a Baerveldt tube resulted in a significant reduction in IOP in association with low complications in comparison to the Ahmed glaucoma valve. 20 The advantage of implanting a BGI instead of an AVG are also related to a higher bleb encapsulation rate reported in the AVG group. The early conjunctival exposure to the proinflammatory me-diators from the aqueous can be a reason for this high encapsulation rate.…”
Section: Discussionmentioning
confidence: 99%
“…The eyeWatch encompasses a mechanism allowing for selective compression of its internal elastic tube, thus altering its fluidic resistance, which is performed noninvasively using the eyeWatch Pen single use during the surgery or the eyeWatch Pen (office) post-operatively. 20,21 In this small case series we assess the efficacy and safety of eyeWatch device in vitrectomized refractory glaucomatous eyes.…”
Section: Introductionmentioning
confidence: 99%
“…172 Additionally, initial clinical results of the eyeWatch have reported an extremely low complication rate (7%). 173 It is believed that the device will prevent IOP spikes and promote smooth transitions of IOP through fine-tuning the flow resistance in a continuous manner, and hence may mitigate the tissue response and FC formation. The eyeWatch allows for non-invasive adjustments of the flow resistance, leading to patient-specific management of IOP and eliminating the need for surgical reinterventions.…”
Section: Subconjunctival Gddsmentioning
confidence: 99%
“…Since the flow resistance can be tuned gradually, the IOP spikes observed in the 2nd wave implants can be reduced, thus the relevant tissue response could be mitigated because the IOP varies in smooth means. 39,173 However, the eyeWatch™ implant doesn't come with an integrated IOP sensor, making it inconvenient for the clinicians to use. Typically, operators need to measure the IOP after each adjustment of the flow resistance to confirm that the desired IOP is reached.…”
Section: Rd Wavemicrosystemmentioning
confidence: 99%